Revision of Pazala Moore, 1888: The Graphium (Pazala) alebion and G. (P.) tamerlanus Groups, with Notes on Taxonomic and Distribution Confusions (Lepidoptera: Papilionidae) - Zhang, Hui-Hong; Cotton, Adam M.; Condamine, Fabien L.; Wang, Rong-Jiang; Hsu, Yu-Feng; Duan, Kuang; Zhang, Xin; Hu, Shao-Ji (Zootaxa, 2020)
Three Graphium species belonging to two species groups of the subgenus Pazala, the alebion and tamerlanus groups, were examined in molecular and morphological studies, and their female genitalia are reported for the first time. Their relationship with other species groups within the subgenus is assessed and their divergence times are estimated. We find that G. (P.) alebion is the first lineage to diverge within Pazala in the early Miocene (20 Ma) and that G. (P.) tamerlanus and G. (P.) parus are sister species and diverged from each other in the late Miocene (7 Ma). A revision of the four recognised taxa belonging to three species is presented, and historical misidentification of these taxa and their geographic ranges are explained.